How much does it cost to live with dignity in Mexico? Tracking the Wellbeing Basket measurement (2019-2024). Regional Comparative Analysis - Jiménez-Bandala, Carlos Alberto; Gael Quiroz, Christian; Laynez Palomeque, Jamnia Joarib (Revista Internacional de Salarios Dignos, 2025)
Measuring the purchasing power of wages involves a complex process: constructing a median consumption basket that approximates a dignified standard of living and tracking it over time to analyze inflationary impacts on impoverishment (loss of purchasing power). This article examines price changes for components of the Wellbeing Basket—developed since 2019 by the International Observatory for Living Wages—now including a regional comparison between Mexico City and Cancún, Quintana Roo (the country’s most important tourist destination). The basket comprises three components to cover food, non-food, and food preparation needs under a dignity-centered framework. Using a basket methodology adjusted to real consumption patterns, data from the first post-neoliberal administration (2019-2024) are compared. Results reveal a sustained rise in the basket’s cost, with significant regional disparities, underscoring the need for public policies that transcend subsistence frameworks and advocate for regionally differentiated minimum wages